2015
DOI: 10.1101/030783
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using genotype data to distinguish pleiotropy from heterogeneity: deciphering coheritability in autoimmune and neuropsychiatric diseases

Abstract: Shared genetic architecture between phenotypes may be driven by a common genetic basis (pleiotropy) or a subset of genetically similar individuals (heterogeneity). We developed BUHMBOX, a well-powered statistical method to distinguish pleiotropy from heterogeneity using genotype data. We observed a shared genetic basis between 11 of 17 tested autoimmune diseases and type I diabetes (T1D, p<10 -12 ) and 11 of 17 tested autoimmune diseases and rheumatoid arthritis (RA, p<10 -7 ). This sharing could not be explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Heterogeneity can occur as the result of many different scenarios including diagnostic misclassifications, molecular subtypes, and excessive comorbidity. We evaluated whether pleiotropy or heterogeneity best explained the high comorbidity rates amongst the five diseases studied using BUHMBOX 20 (see Methods ). BUHMBOX detects heterogeneity by calculating the cross-locus correlation of disease B-associated loci among disease A cases; a non-zero correlation is indicative of heterogeneity 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneity can occur as the result of many different scenarios including diagnostic misclassifications, molecular subtypes, and excessive comorbidity. We evaluated whether pleiotropy or heterogeneity best explained the high comorbidity rates amongst the five diseases studied using BUHMBOX 20 (see Methods ). BUHMBOX detects heterogeneity by calculating the cross-locus correlation of disease B-associated loci among disease A cases; a non-zero correlation is indicative of heterogeneity 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Next, those phenotypes with significant genetic correlation with HIV acquisition were tested to see if they were driven by genome-wide pleiotropy or by overlap with a subset of HIV cases. Here, BUHMBOX was used to perform an analysis of heterogeneity within the cases 25 , making use of their known genome-wide significant SNPs. These SNPs came from the largest and most recent GWAS of these phenotypes, an analysis of 34,241 cases of schizophrenia 35 and of 86,640 cases of inflammatory bowel disease (which also included ulcerative colitis) 36 .…”
Section: Resultsmentioning
confidence: 99%
“…To better understand the cause of any genetic overlaps between HIV acquisition and genetically overlapping phenotypes, we used BUHMBOX to test if genetic correlations were driven by pleiotropy or heterogeneity 25 . BUHMBOX compares LD between known associated SNPs for trait-1 in both cases and controls for trait-2.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent to our investigations [158] have developed another promising approach to investigate genetic heterogeneity. Their approach differs from the one presented here.…”
Section: Discussionmentioning
confidence: 99%
“…Some merely aimed at identifying the presence of genetic heterogeneity in a population [158], while others had the more ambitious goal of identifying genetic subtypes and grouping individuals accordingly [159]. However, while Arnedo et al [159] reported to find evidence for distinct schizophrenia subtypes, this claim has been heavily disputed on a number of grounds (see PubMed discussion at http://www.ncbi.nlm.nih.gov/pubmed/25219520).…”
Section: Introductionmentioning
confidence: 99%